A SURVIVAL ANALYSIS ON THE IMMUNE LANDSCAPE OF PAEDIATRIC SOLID TUMOURS. - Khushboo Shrivastava; Tongbram Soni Devi; Saket Verma; P. Jaiswal; Tirumala Kanakadurga Sripati (Student's Journal of Health Research Africa, 2023)
Introduction: The functional orientation of the tumor microenvironment has been shown in large immunogenomic investigations to play a predictive role in adult solid tumors; however, the paediatric equivalent of this variable has received little attention. Method: For four paediatric tumor types (408 patients), Wilms tumor (WLM), neuroblastoma (NBL), os- teosarcoma (OS), clear cell sarcoma of the kidney (CCSK), and rhabdoid tumor of the kidney (RT), we carried out a thorough study of public RNAseq data (TARGET). We evaluated the Immunologic Constant of Rejection’s (ICR) capability to detect an active Th1/cytotoxic response. Additionally, we carried out gene set enrichment analysis (ssGSEA), grouped more than 100 immunological features with good characterization into distinct immune subtypes, and compared the results. Result: Higher ICR scores were linked to better OS and high-risk NBL without MYCN amplification survival, but worse WLM survival. The same four major modules previously discovered in adult tumors (TCGA) were revealed by clustering immunological characteristics. These modules classified paediatric patients into six immunological subtypes (S1–S6), each of which had a different prognosis for survival. The S2 cluster, which has low enrichment of the wound healing signature, high Th1, and low Th2 infiltrates, and the S4 cluster, which has the opposite characteristics, demonstrated the best overall survival. Increased T-cell infiltration and worse outcomes were linked to the WNT/Beta-catenin pathway in OS. Conclusion: We showed that extracranial paediatric tumors might be categorized by their immunological makeup, revealing parallels with tumors seen in adults. To find diagnostic and prognostic biomarkers and to find potential immune-responsive tumors, immunological factors may be investigated. Recommendations: Close disease surveillance and genetic evaluation are recommended for patients with certain solid tumors or particular predisposing conditions.